A critical appraisal on the recurrence of sandalwood spike disease and its management practices. Issue 6 (4th November 2020) - Mondal, Soma; Sundararaj, Ramachandran; Yashavantha Rao, H. C.
Abstract: Sandal ( Santalum album ) is an important forest tree that has been utilized for centuries, valued for its wood and scented essential oil derived from the heartwood. Sandalwood spike disease (SSD) is one of the most destructive problems that affect Indian sandalwood. In 1969, three research groups confirmed that the causal agent of SSD was a phytoplasma. Although research literature on sandalwood spike disease has been published for over a century, many earlier publications reported only primarily descriptive macro‐morphological data. Identification of the causal agent was confirmed only recently, using nested PCR of 16S rRNA‐encoding gene sequences and restriction fragment length polymorphism (RFLP) analysis. The identified phytoplasma exhibited high sequence similarity to the aster yellows subgroup 16SrI‐B in NCBI BLAST search. The use of tissue culture in transgenic and disease‐free cloning strategies to produce disease‐resistant sandalwood tress might be the most realistic solution for SSD. The aim of this review is to increase understanding of SSD among phytopathologists in order to encourage research on SSD to discover best management practices. The increased cultivation of sandalwood plantations has significant importance, and it is essential to review the status of SSD.